2010
DOI: 10.1186/1471-2105-11-229
|View full text |Cite
|
Sign up to set email alerts
|

GOAL: A software tool for assessing biological significance of genes groups

Abstract: BackgroundModern high throughput experimental techniques such as DNA microarrays often result in large lists of genes. Computational biology tools such as clustering are then used to group together genes based on their similarity in expression profiles. Genes in each group are probably functionally related. The functional relevance among the genes in each group is usually characterized by utilizing available biological knowledge in public databases such as Gene Ontology (GO), KEGG pathways, association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Gene ontology enrichment analysis [30] revealed that genes down-regulated after Fusarium infection are predicted to mainly contribute toward growth and other primary metabolic …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene ontology enrichment analysis [30] revealed that genes down-regulated after Fusarium infection are predicted to mainly contribute toward growth and other primary metabolic …”
Section: Resultsmentioning
confidence: 99%
“…The association between Affy probe ID and UniGene from NCBI were updated, which resulted in 45,699 associations mapping to 26,674 unique UniGenes. Ensemble Plants (version 22) gene ontology association with wheat genes was analyzed for gene enrichment using the GOAL software [30].…”
Section: The Datasetsmentioning
confidence: 99%
“…aBiclusters identified by biDCG, as marked on Figure 5.bNumber of GO terms enriched in the gene set, with a significance level better than 0.05: GOAL [48] results.cNumber of functional terms enriched in the gene set, with a significance level better than 0.05: DAVID [49] results.dWe regrouped all genes from NL_A, NL_B, and NL_C, as those correspond to healthy patients.…”
Section: Resultsmentioning
confidence: 99%
“…The less conserved gene group consists of 171 human genes whose FPSIs are 0.0 (no common TF) when human is compared with both chimpanzee and mouse (Supplemental File 5). We then performed a gene functional characterization of each group using Gene Ontology AnaLyzer (GOAL) [36]. This reveals that the genes with more conserved promoters are closely related with various developmental process (GO:0007275, GO:0032502, GO:0048856, GO:0048731, GO:0009653, GO:0048513, GO:0001822), while genes with less conserved promoters are related with regulation of transport, protein binding and signalling (GO:0051050, GO:0005515, GO:0007242, GO:0019932, GO:0032501) and their functional representations are less significant even though there are twice number of genes in this group than in the most conserved group (Supplemental File 5).…”
Section: Functional Characterizationmentioning
confidence: 99%